Sociology 685: SOCIOLOGY OF VIOLENCE - Collins, Randall (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Sociology 685 is a seminar offered intermittently in the Sociology Department, University ofPennsylvania. We examine a variety of topics through exploring both classic and recent literature, with an emphasis on micro-sociological processes of interaction. We use both videos and still photos of violent confrontations, and some audio recordings where available. Our methods are to analyze these materials closely using techniques of studying emotional cues in facial expressions and body postures, conversational rhythms and other auditory patterns, and in general the apparatus of contemporary microsociology.